2016
DOI: 10.1097/txd.0000000000000594
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal for Early Dosing Regimens in Heart Transplant Patients Receiving Thymoglobulin and Calcineurin Inhibition

Abstract: There is currently no consensus regarding the dose or duration of rabbit antithymocyte globulin (rATG) induction in different types of heart transplant patients, or the timing and intensity of initial calcineurin inhibitor (CNI) therapy in rATG-treated individuals. Based on limited data and personal experience, the authors propose an approach to rATG dosing and initial CNI administration. Usually rATG is initiated immediately after exclusion of primary graft failure, although intraoperative initiation may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…Our group recently published a review that concluded, based on 2 published studies [ 33 , 61 ], that a maximum total rATG dose of 7.5 mg/kg is adequate in children at standard immunological risk receiving CNI-based maintenance therapy [ 13 ]. A lower cumulative dose (but not less than 3.5 mg/kg) may be sufficient in younger, lower-risk patients who are receiving CNI therapy, in view of the increased risk for PTLD in the youngest recipients [ 8 , 13 ], although this has not been assessed clinically. The duration of rATG infusion should not be less than 6 h [ 13 ].…”
Section: Ratg Dosing and Monitoring In Pediatric Heart Transplantatiomentioning
confidence: 99%
See 2 more Smart Citations
“…Our group recently published a review that concluded, based on 2 published studies [ 33 , 61 ], that a maximum total rATG dose of 7.5 mg/kg is adequate in children at standard immunological risk receiving CNI-based maintenance therapy [ 13 ]. A lower cumulative dose (but not less than 3.5 mg/kg) may be sufficient in younger, lower-risk patients who are receiving CNI therapy, in view of the increased risk for PTLD in the youngest recipients [ 8 , 13 ], although this has not been assessed clinically. The duration of rATG infusion should not be less than 6 h [ 13 ].…”
Section: Ratg Dosing and Monitoring In Pediatric Heart Transplantatiomentioning
confidence: 99%
“…A lower cumulative dose (but not less than 3.5 mg/kg) may be sufficient in younger, lower-risk patients who are receiving CNI therapy, in view of the increased risk for PTLD in the youngest recipients [ 8 , 13 ], although this has not been assessed clinically. The duration of rATG infusion should not be less than 6 h [ 13 ].…”
Section: Ratg Dosing and Monitoring In Pediatric Heart Transplantatiomentioning
confidence: 99%
See 1 more Smart Citation
“…The immunological risk and the presence of infection influence the initial CNI target levels. ATG and CNIs should not overlap except in high‐risk cases …”
Section: Induction Therapy and Delayed Use Of Cnimentioning
confidence: 99%
“…ATG and CNIs should not overlap except in high-risk cases. 26 Anti-IL2 RA allows a delayed start of CNIs after HTx with a lower rate of renal failure and without an increased risk of acute rejection. 27 Delgado et al 28 compared HTx patients who received ATG or anti-IL2 RA induction (both with delayed CsA).…”
Section: Induction Therapy and Delayed Use Of Cnimentioning
confidence: 99%